The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1161/circulationaha.107.733212
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Activity of Lysosomal Carboxypeptidase (Cathepsin) A Is Required for Proper Elastic Fiber Formation and Inactivation of Endothelin-1

Abstract: Background— Lysosomal carboxypeptidase, cathepsin A (protective protein, CathA), is a component of the lysosomal multienzyme complex along with β-galactosidase (GAL) and sialidase Neu1, where it activates Neu1 and protects GAL and Neu1 against the rapid proteolytic degradation. On the cell surface, CathA, Neu1, and the enzymatically inactive splice variant of GAL form the elastin-binding protein complex. In humans, genetic defects of CathA cause galactosialidosis, a metabolic disease c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 38 publications
1
92
0
1
Order By: Relevance
“…27 Because increased proteolytic activity of cell-surface-delivered PPCA in transfected cells could potentially inactivate other mitogenic polypeptides (eg, endothelin-1 or angiotensin II), 83,84 results obtained from such an experimental model might not be conclusive. However, we demonstrated that treatment of cultured human AoSMCs with blocking antibody raised to human Neu 1 22 or with the competitive sialidase inhibitor ddNANA, which inhibits the activity of Neu1, 27 induced a significant up-regulation in their proliferation in response to fetal bovine serum.…”
Section: Figure 5 Results Of [mentioning
confidence: 99%
“…27 Because increased proteolytic activity of cell-surface-delivered PPCA in transfected cells could potentially inactivate other mitogenic polypeptides (eg, endothelin-1 or angiotensin II), 83,84 results obtained from such an experimental model might not be conclusive. However, we demonstrated that treatment of cultured human AoSMCs with blocking antibody raised to human Neu 1 22 or with the competitive sialidase inhibitor ddNANA, which inhibits the activity of Neu1, 27 induced a significant up-regulation in their proliferation in response to fetal bovine serum.…”
Section: Figure 5 Results Of [mentioning
confidence: 99%
“…In particular, the components of the multienzyme complex, Neu1, CathA, and ␤-galactosidase (or its alternatively spliced elastin-binding form), participate in processing of endothelin-1 (21,33), assembly of the elastic fibers (21,34,35), pro-inflammatory response in macrophages (36), migration, invasion, and adhesion of cancer cells (37), proliferation of aortic smooth muscle cells (38), and exocytosis (39). In humans, genetic defects in CathA cause disruption of the complex and trigger galactosialidosis (MIM 256540), a severe multisystemic disease characterized by combined deficiency of Neu1, ␤-galactosidase, and CathA (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Animals-CathA S190A mice carrying the point c.571AGCϾGCA (S190A) mutation in the CathA gene and CathA S190A-Neo mice carrying, in addition, a PGK-Neo cassette in intron 7 were generated through the targeted disruption of the CathA gene as described (21). The CathA S190A-Neo and CathA S190A mice ranging from 4 to 12 weeks of age were compared with the appropriate wild-type (WT) littermate controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations